2017
DOI: 10.1097/ta.0000000000001282
|View full text |Cite
|
Sign up to set email alerts
|

Model of trauma-induced coagulopathy including hemodilution, fibrinolysis, acidosis, and hypothermia

Abstract: A new model of TIC is created. Contribution of various constituents to pathogenesis of TIC and their interactions are evaluated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 29 publications
0
35
0
Order By: Relevance
“…Additionally, we found that acidemia at the time of admission is associated with mortality. Acidemia (pH < 7.20) may contribute to worsened trauma-induced coagulopathy and mortality, as previously described [ 17 - 18 ].…”
Section: Discussionmentioning
confidence: 65%
“…Additionally, we found that acidemia at the time of admission is associated with mortality. Acidemia (pH < 7.20) may contribute to worsened trauma-induced coagulopathy and mortality, as previously described [ 17 - 18 ].…”
Section: Discussionmentioning
confidence: 65%
“…12 In our study, we found that lower pH and lower prothrombin time in percentage (Quick) were associated with a higher number of RBC units transfused. In the study by Shenkman et al, 13 metabolic acidosis was a risk factor for clot formation and impaired platelet function; moreover, it was associated with systemic disseminated intravascular coagulation. 14 In clinical practice, acidosis has been shown to be an independent risk factor for RBC transfusion.…”
Section: Discussionmentioning
confidence: 96%
“…, Shenkman et al . ). The accumulation of catecholamines and metabolites after injury, the extent of endothelial activation and the host immune response also affect the phenotype of TIC (Cohen et al .…”
Section: Acquired Hyperfibrinolysismentioning
confidence: 97%
“…Trauma-induced coagulopathy (TIC) is a term used to describe the spectrum of coagulation changes that occur following severe injury (Hess et al 2008). There are multiple phenotypes of TIC, and the clinical manifestation is influenced primarily by thrombin production, platelet function and fibrinolysis (Moore et al 2015, Shenkman et al 2017. The accumulation of catecholamines and metabolites after injury, the extent of endothelial activation and the host immune response also affect the phenotype of TIC (Cohen et al 2009, Johansson et al 2012, Johansson et al 2017.…”
Section: Acute Traumatic Coagulopathymentioning
confidence: 99%